Monetary Reference Points of Managers – Empirical Evidence of Status Quo Preferences and Social Comparisons. (6th November 2015) - Grund, Christian; Martin, Johannes
Abstract: We explore whether monetary reference points affect managers′ job satisfaction. These reference points include a manager′s own status quo and the incomes of comparable managers within the same firm and also at the market level. Making use of a unique panel data set of managers in the German chemical sector, we find that social comparisons of compensation do affect reported job satisfaction. Both the relative income position within a manager's own firm and a manager's wage rank on the market have positive relations with job satisfaction. There is no evidence of the relevance of status quo considerations once we control for firm‐related pay variables.